The Best Effort System to Score Subjective Answers of Tests in a Large Group - Lee, Jae-Young; ., . (International Journal of Engineering and Technology, 2018)
The subjective tests can improve the quality of education by measuring the cognitive abilities, but the biggest drawback is the lack of fairness, consistency, and accuracy. To improve the drawback, we proposed the best effort system that scores the correct subjective answers based on the correct answer table made by committee members, then classifies the rest of subjective answers into groups of similar answers so that the latest automatic scoring systems and graders assign each reasonable credit to each group of similar subjective answers.In the scoring system, the groups of the similar answers are evaluated by raters and the latest automatic scoring systems, such as syntax tree comparison grading, and the syntax and semantic tree-oriented grading. All the scores for each similar answer are added and then an average for each similar is stored in the similar answer table. Finally, the system grades applicantâ€™s answers using the correct answer table and the similar answer table. This paper proposes the algorithm for the best effort scoring system to include the latest automatic scoring system in order to be as fair, consistent, and accurate as possible.Â Â